Edukasi Pencegahan Bullying Melalui Permainan Ular Tangga Untuk Meningkatkan Pengetahuan Siswa Di SDIT Cendikia Andalas Padang - Hamidatul Yuni; Siti Nur Hasanah (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Padang Timur District has the second-highest number of cases of child violence in Padang City, with 50% occurring in elementary school students and below. This program aims to improve students' knowledge about bullying prevention at SDIT Cendikia Andalas, one of the elementary schools in Padang Timur District. This activity uses a pre-experimental method with a One-Group Pretest–Posttest Design. The target of this activity is 23 fifth-grade students. The use of engaging media, such as the Snakes and Ladders game, to educate elementary school-aged children about bullying is one effective way to improve their knowledge. Evaluation of student knowledge is conducted using pretest and posttest questionnaires, which are then analyzed using a paired t-test. The results of the activity show that students' knowledge increased after playing the Snakes and Ladders game, as indicated by an increase in the average score from 17.00 (pretest) to 19.52 (posttest) with a p-value of 0.000. These findings suggest that the game is effective in enhancing students' understanding of various forms of bullying and strategies for prevention. Using the Snakes and Ladders game as a teaching tool is a good way to teach elementary school children how to prevent bullying. As an applied recommendation, this media can be used by teachers and schools as an engaging learning tool to strengthen bullying prevention efforts in the classroom.